2018
DOI: 10.1007/s00113-018-0533-4
|View full text |Cite
|
Sign up to set email alerts
|

Humerusschaftfraktur

Abstract: There is still no gold standard for the treatment of humeral shaft fractures. This might be attributed to the fact that several commonly used treatment methods have shown good clinical results. A bimodal age distribution of humeral shaft fractures with frequency peaks between 20 and 30 years old and above 60 years old is reported. Decision making for conservative or operative treatment depends not only on the injury pattern but is also dependent on individual patient needs. Currently available operative techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
5
0
4
Order By: Relevance
“…The fractures of the humeral shaft make up about 1–3% of all skeletal fractures, and belong to the group of the most common bone injuries ( 1 – 4 ). The incidence increases with age and may be associated with significant in-patient mortality and health care utilization costs ( 2 , 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fractures of the humeral shaft make up about 1–3% of all skeletal fractures, and belong to the group of the most common bone injuries ( 1 – 4 ). The incidence increases with age and may be associated with significant in-patient mortality and health care utilization costs ( 2 , 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of progression to non-union of open fractures in our study was six-fold higher compared to closed fractures reported in the literature. 8,28,29 Fractures of the humeral shaft lead to radial nerve damage in 8% to 12% of cases. 11,30 In the present study, radial nerve palsy was found in 14.4% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of progression to non-union of open fractures in our study was six-fold higher compared to closed fractures reported in the literature. 8,28,29…”
Section: Discussionmentioning
confidence: 99%
“…Younger populations have high-intensity mechanisms, while older populations have low-energy falls. There are two damage peaks in the third and sixth decades [7][8][9]. Between 13.4 and 14.5 per 100,000 per year for each age group, the incidence rate quickly increased to around 90 per 100,000 by the ninth decade [10].…”
Section: Introductionmentioning
confidence: 99%